Closure and post-closure of landfills in Malaysia: lessons learnt - S.H, Fauziah; P., Agamuthu (Malaysian Journal of Science, 2010)
The disposal of approximately 90% of more than 30,000 tonnes of municipal solid waste (MSW) generated daily into 167 sanitary and non-sanitary landfills depict the importance of landfill in Malaysia. The objective of this paper is to explore issues pertaining to the closure and post-closure of landfills in Malaysia using four types of disposal facilities. The closure of a properly planned Air Hitam Sanitary Landfill (AHSL) saw the management of the closure and post-closure activities at the utmost efficiency. The landfill has become the blueprint of energy conversion technology with a capability of 2MW. Unfortunately, closure of non-sanitary disposal sites were not as successful as that in AHSL. Kundang landfill, a non-sanitary landfill was ordered to be closed immediately in 2007 since it continues to contaminate the surrounding area. Regardless of its non-active status, untreated leachate with 280 440.00 giday of COD pollutes the river which may affect the environmental quality of the area. Similar scenario was also observed at other sites, namely two reclaimed ex-mining land for commercial and residential area. One was operating as dumping area before its closure in 2000. It was developed and converted into residential and commercial area including terrace houses, high rise apartments, and commercial buildings. Improper planning of the closure resulted with contamination of arsenic (64.4 mg/kg) and mercury (11.5 mg/kg) to the surrounding soil. Another case study saw extensive reclamation of an ex-mining pond with MSW including domestic, industrial, and construction debris. The lack of appropriate planning of the conversion of the land-use resulted with contamination of surface water with hydrogen sulphide alarmed the residents. The area recorded presence of hydrogen sulphide gas which reached approximately 200 ppm. Thus, it can be concluded that proper closure and post-closure strategies are crucial for landfills and disposal sites. The need for proper policies and .Mines on post-closure and the uniformity of these regulations would ensure standardised landfill remediation with minimal environmental impacts.